Gender differences in behavioural changes induced by latent toxoplasmosis - Lindová, Jitka; Novotná, Martina; Havlícek, Jan; Jozífková, Eva; Skallová, Anna; Kolbeková, Petra; Hodný, Zdenek; Kodym, Petr; Flegr, Jaroslav (International journal for parasitology, 2006)
There is growing evidence that the protozoan Toxoplasma gondii modifies behaviour of its intermediate hosts, including humans, where it globally infects about 20-60% of the population. Although it is considered asymptomatic in its latent stage, it was previously found to have remarkable and gender different effects on the personality factors A (warmth), G (rule consciousness), L (vigilance, mistrust) and Q3 (self-control, self-image) from Cattell's 16PF Questionnaire. We performed a double blind experiment testing 72 and 142 uninfected men and women, respectively, and 20 and 29 infected men and women, respectively, in order to verify these gender differences using behavioural experiments. Our composite behavioural variables Self-Control and Clothes Tidiness (analogue to the 16PF factors G--conscientiousness and Q3--self-control) showed a significant effect of the toxoplasmosis-gender interaction with infected men scoring significantly lower than uninfected men and a trend in the opposite direction in women. The effect of the toxoplasmosis-gender interaction on our composite behavioural variable Relationships (analogue to factor A--warmth) approached significance; infected men scored significantly lower than uninfected men whereas there was no difference in women. In the composite behavioural variable Mistrust (analogue to factor L), the pattern was affected by environment (rural versus urban). Possible interpretations of the gender differences are discussed.
Keywords: Male; Self Concept; Interpersonal Relations; sexuální faktory; sebepojetí; odívání; Adult; interpersonální vztahy; dospělí; toxoplazmóza; mužské pohlaví; Trust; Behavior; chování; dvojitá slepá metoda; Personality; lidé; Toxoplasmosis; ženské pohlaví; osobnost; Humans; Sex Factors; důvěra; Clothing; Double-Blind Method; Female